A Review of Techniques to Enhance an Amplifier’s Performance Using Resistive Local Common Mode Feedback - Jaime Ramirez-Angulo; Antonio J. Lopez-Martin; Ramón G. Carvajal; Antonio Torralba; Jesus Huerta-Chua (Eng, 2023)
A review of some of the most common applications of the resistive local common mode feedback technique to enhance amplifier’s performance is presented. It is shown that this simple technique offers essential improvement in open loop gain, gain-bandwidth product, slew rate, common mode rejection ratio, power supply rejection ratio, etc. This is achieved without increasing power dissipation or supply voltage requirements and with small additional silicon area and circuit complexity. It is also shown that it is especially appropriate to improve amplifiers’ performance in current fine-line submicrometer CMOS technology. Some of the applications discussed are GB enhanced, class AB and super class AB operational amplifiers, gain boosted op-amps, bulk-driven circuits, sample and hold circuits and power management circuits, among others.